Extraction of Sodium Picrate by 3m-Crown-m Ethers and Their Monobenzo Derivatives (m = 5, 6) into Benzene: Estimation of Their Equilibrium-Potential Differences at the Less-Polar Diluent/Water Interface by an Extraction Method. (13th June 2016) - Kudo, Yoshihiro; Nakamori, Tsubasa; Numako, Chiya
Abstract : Individual distribution constants (K D, A ) of picrate ion (Pic − ) and extraction constants (K e x ± ) of NaPic by some crown ethers (L) into benzene (Bz) at 25°C were calculated from data reported previously. These constants were defined asK D, P i c = P i c - o / [ P i c - ] andK e x ± = N a L + o P i c - o / ( N a + L o [ P i c - ] ), respectively. Here, the subscript "o" denotes an organic (o) phase and practically o = Bz. 15-Crown-5 ether (15C5), 18-crown-6 one (18C6), and their monobenzo (B) derivatives (B15C5 and B18C6) were selected as L. Interfacial equilibrium-potential differences (Δ ϕ e q ) at extraction were estimated at 298 K. A plot oflog ⁡ K e x ± versus- Δ ϕ e q for the four L extraction systems gave a straight line with slope = 84 V −1 . This slope was compared with those, reported before, of the dichloromethane (DCM), 1, 2-dichloroethane (DCE), and nitrobenzene (NB) extraction systems. The slopes of the regression lines were in the order NB < DCM ≤ DCE < Bz. Also, the individual distribution constants of the complex ionN a L + and an ion-pair complex (N a L + P i c - ) into Bz phase were calculated from the above extraction data. At least, a comparison between these values suggests that Bz molecules mainly interact withN a L + moiety ofN a L + P i c - .